Evaluation of Torque, Electromyographic Activity and Neuromuscular Efficiency of the Internal Oblique Muscle in Pilates Practitioners - Panhan, Ana C. (2022)
Background. The present study aimed to evaluate the neuromuscular efficiency (NME) of the internal oblique (IO) muscle through electromyography (EMG) analysis, torque test in practitioners and non-practitioners (control) of Pilates. Methods. Participants included 40 health women: Pilates practitioners (n = 20) and non-practitioners (n = 20). They were tested for trunk flexion (torque). Their internal oblique IO muscle (both sides) was submitted to EMG to estimate its NME. Results concerning EMG and NME were compared between practitioners and control. Results. Statistical analysis (Student t-test; p < 0.05) showed significant difference in torque in N.m (p = 0.00083), NME (p = 0.00044) and EMG in microvolts (p = 0.0015) values between practitioners (93.6 ± 17.8, 0.77 ± 0.48, 153.4 ± 65.3, respectively) and control (65.5 ± 19.4, 0.27 ± 0.10, 268.2 ± 81.0, respectively). Conclusions. Our results suggest Pilates exercises are effective in training the IO muscle to improve the NME in women engaged in Pilates exercises 2 times a week.